Auxiliary facility spaces a descriptive case study on user satisfaction and user preference in parishes from the archdiocese of Davao - Ababa, Rizza May O. (2021)
To most people, religious architecture only refers to the church building itself. To their not-knowing, there are other auxiliary buildings aside from the church building itself in religious architecture such as the pastoral residence and administrative offices. It is undeniable that these spaces need be guaranteed as a productive working spaces for its users which are the parish staff, mandated organization members and the parishioners. By using the Person-Environment Fit Theory, this research analyzed user satisfaction and user preference for ambient conditions and facility design of church auxiliary facilities from parishes in the Archdiocese of Davao. The study aims to collect data that could help determine what the users prefer that would align with their needs. Through quantitative and qualitative research, the parishes studied include Immaculate Conception Parish in Mintal, Sacred Heart of Jesus Parish in Obrero, San Isidro Labrador Parish in Catalunan Grande, San Lorenzo Ruiz Parish in Talomo, Sr. San Antonio De Padua Parish in Agdao, and Virgen De Los Remedios Parish in Toril. Data and results were analyzed in a descriptive manner and frequency analysis. These methods were used to enrich the reliability of the collected data from the study areas. The analysis of data was used as a basis to formulate the architectural guidelines for the proposed auxiliary facility building of parishes in the Archdiocese of Davao.